Downregulation of PDK4 Increases Lipogenesis and Associates with Poor Prognosis in Hepatocellular Carcinoma - Yang, Chen (J Cancer, 2019)
Alterations in cellular metabolism are one of the characteristics in cancer. They are not only the result of tumor progression but also the cause of cancer initiation. Pyruvate dehydrogenase kinase 4 (PDK4) is a key metabolic enzyme, which regulates cell metabolism by inhibiting pyruvate dehydrogenase (PDH). However, the function and regulating mechanism of PDK4 in HCC remain unclear. Here, we found that the expression of PDK4 was significantly decreased in HCC tissues, and its downregulation could predict poor prognosis of HCC patients. Silencing PDK4 significantly facilitated proliferation and migration of HCC cells. Knockdown of PDK4 didn't influence the oxidative phosphorylation and glycolysis capacity of HCC cells in vitro. However, knockdown of PDK4 increased expression of key lipogenic enzymes, fatty acid synthase (FASN) and stearoyl-CoA desaturase (SCD), which finally induced lipogenesis. These data suggest that PDK4 inhibits proliferation and migration of HCC cells probably via suppressing lipogenesis.